Workplace interventions for common mental disorders: a systematic meta-review. Issue 4 (1st December 2015) - Joyce, S.; Modini, M.; Christensen, H.; Mykletun, A.; Bryant, R.; Mitchell, P. B.; Harvey, S. B.
Abstract : Depression and anxiety disorders are the leading cause of sickness absence and long-term work incapacity in most developed countries. The present study aimed to carry out a systematic meta-review examining the effectiveness of workplace mental health interventions, defined as any intervention that a workplace may either initiate or facilitate that aims to prevent, treat or rehabilitate a worker with a diagnosis of depression, anxiety or both. Relevant reviews were identified via a detailed systematic search of academic and grey literature databases. All articles were subjected to a rigorous quality appraisal using the AMSTAR assessment. Of the 5179 articles identified, 140 studies met the inclusion criteria, of which 20 were deemed to be of moderate or high quality. Together, these reviews analysed 481 primary research studies. Moderate evidence was identified for two primary prevention interventions; enhancing employee control and promoting physical activity. Stronger evidence was found for CBT-based stress management although less evidence was found for other secondary prevention interventions, such as counselling. Strong evidence was also found against the routine use of debriefing following trauma. Tertiary interventions with a specific focus on work, such as exposure therapy and CBT-based and problem-focused return-to-work programmes, had a strong evidence base for improving symptomology and a moderate evidence base for improving occupational outcomes. Overall, these findings demonstrate there are empirically supported interventions that workplaces can utilize to aid in the prevention of common mental illness as well as facilitating the recovery of employees diagnosed with depression and/or anxiety.